"That's My Job": Comparing the Beliefs of More and Less Accomplished Special Educators Related to Their Roles and Responsibilities. (November 2015) - Urbach, Jennifer; Moore, Brooke A.; Klingner, Janette K.; Galman, Sally; Haager, Diane; Brownell, Mary T.; Dingle, Mary
The purpose of this study is to understand special education teachers' beliefs regarding their roles and responsibilities and to determine how these beliefs differ among more and less accomplished teachers. In this study, the authors examine the interviews of special education teachers identified as either more or less accomplished based on the Reading in Special Education (RISE) observation instrument. Through qualitative coding of the data, several themes about beliefs revealed differences between the teachers. The more accomplished teachers discussed a need for instructional intensity and linked their roles and responsibilities to academic needs. Furthermore, a sense of high efficacy was seen in more accomplished teachers' discussion of teaching regardless of outside influences. Less accomplished teachers focused on building relationships and protecting their students. Findings point to the importance of looking closely at beliefs and their impact on teacher practice.